Distribution of Bivalves in Intertidal Zone of Belimbing Bay of Pesisir Selatan Regency, West Sumatra Province - Juliando Saputra; Afrizal Tanjung; Elizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in December 2015 in the Belimbing Bay coastal area of the PesisirSelatan Regency, West Sumatra Province. The purpose of study was to determine the distribution andabundance of bivalves in the intertidal zone. Bivalves samples were taken by using Quadrant TransectSampling Method, in which at each station had one line transect, divided into three plots with a size of3x3 m2, respectively. The study found the abundance of the bivalves at station I (middle zone) washigher (0.15 ind/m2) than in the lower zone (0.07 ind/m2). In station II the lower zone was 0.07 ind/m2lower while the middle zone was 0.16 ind/m2. In station III the highest abundance was in the middlezone (0.15 ind/m2) and the lowest abundance was in the lower zone (0.08 ind/m2). The highest organicmatter content in the station I was 6.97% and the lowest was in the upper zone (4.85%). The lowestorganic matter at station II was lower zone (5.48%), followed by the upper zone (5.74%), and thehighest is in the middle zone (5.96%). At station III, the highest organic matter was 5.54% andfollowed by the lower zone 5.22%, the lowest contained is in the upper zone (5.12%).Keywords: Bivalves, Distribution, Abundance, Belimbing Bay, West Sumatera.